2020
DOI: 10.3171/2019.9.focus19699
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsy for pediatric diffuse midline glioma: a review of circulating tumor DNA and cerebrospinal fluid tumor DNA

Abstract: Diffuse midline glioma (DMG) is a highly malignant childhood tumor with an exceedingly poor prognosis and limited treatment options. The majority of these tumors harbor somatic mutations in genes encoding histone variants. These recurrent mutations correlate with treatment response and are forming the basis for molecularly guided clinical trials. The ability to detect these mutations, either in circulating tumor DNA (ctDNA) or cerebrospinal fluid tumor DNA (CSF-tDNA), may enable noninvasive molecular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…[87] However, emerging studies have reported the detection of tumor specific mutations in the cfDNA of patients with glioma ( Table 2). [87,[98][99][100][101][102][103][104][105][106][107][108][109][110] Detection of glioma specific alterations such as telomerase reverse transcriptase (TERT), [105,111] EGFRvIII, [102] IDH1, [108] and histone mutations [112] has shown promise in minimally invasive diagnosis, molecular profiling, and classification of tumors. Epidermal growth factor receptor (EGFR) gene is amplified in 30-40% of GBMs and nearly 50% of them express the in-frame deleted variant of EGFR receptor, EGFRvIII, and represents an aggressive subtype of GBM.…”
Section: Circulating Tumor Dnamentioning
confidence: 99%
“…[87] However, emerging studies have reported the detection of tumor specific mutations in the cfDNA of patients with glioma ( Table 2). [87,[98][99][100][101][102][103][104][105][106][107][108][109][110] Detection of glioma specific alterations such as telomerase reverse transcriptase (TERT), [105,111] EGFRvIII, [102] IDH1, [108] and histone mutations [112] has shown promise in minimally invasive diagnosis, molecular profiling, and classification of tumors. Epidermal growth factor receptor (EGFR) gene is amplified in 30-40% of GBMs and nearly 50% of them express the in-frame deleted variant of EGFR receptor, EGFRvIII, and represents an aggressive subtype of GBM.…”
Section: Circulating Tumor Dnamentioning
confidence: 99%
“…In addition, the availability of targeted therapy has increased the need for longitudinal monitoring of molecular changes within tumors in order to precisely guide anti-cancer treatment. Hence, there is a compelling need for the indirect assessment of tumors at certain time points via less-invasive tumor markers which can be gained from body fluids of the patient [ 6 , 7 ]. The most proximal source for liquid biopsy for pediatric brain tumors is the cerebrospinal fluid (CSF) followed by peripheral blood including its components serum/plasma and urine [ 8 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple different molecular structures have been identified in the liquids of pediatric brain tumor patients and raised the interest of the scientific field. These biomarkers include circulating tumor cells (CTCs) [ 18 , 19 ], circulating tumor DNA (ctDNA) [ 7 , 18 , 19 ], cell-free DNA (cfDNA) [ 6 , 18 , 19 , 20 , 21 ], circulating proteins [ 6 , 8 , 19 , 20 ], extracellular vesicles and exosomes [ 5 , 18 , 22 , 23 , 24 , 25 , 26 ], micro-RNAs (miRNAs) [ 5 , 19 , 27 , 28 , 29 , 30 , 31 , 32 ], long non-coding RNA (lncRNA) [ 33 ] and other genetic alterations [ 28 , 34 , 35 , 36 , 37 , 38 ]. Detection of these biomolecules may offer advantages compared to surgical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Current applications of liquid biopsy for glioblastoma diagnosis have to be improved for two main reasons: although in normal physiological conditions the BBB prevents ctDNA circulating into the blood, in pathological situations (i.e., presence of glioblastoma) the BBB is disrupted, which allows for EVs and other cell-free nucleic acids to cross it; and the detection of all cell-free nucleic acids remains a challenge due to the low amounts in the blood in the early course of the disease [2]. However, various new approaches and methods are being developed, such as detecting cell-free nucleic acids (cfDNA and cfRNA) with digital droplet PCR (ddPCR) [99,100] and stabilizing cell-free nucleic acids in the blood [101]. With the development of more sensitive methods, the forthcoming diagnosis of glioblastomas with liquid biopsy will be less demanding.…”
Section: Cell Free Circulating Tumor Dnamentioning
confidence: 99%